2021
DOI: 10.1136/bmjopen-2020-047001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating evaluation frameworks: a scoping review of frameworks for assessing health apps

Abstract: ObjectivesDespite an estimated 300 000 mobile health apps on the market, there remains no consensus around helping patients and clinicians select safe and effective apps. In 2018, our team drew on existing evaluation frameworks to identify salient categories and create a new framework endorsed by the American Psychiatric Association (APA). We have since created a more expanded and operational framework Mhealth Index and Navigation Database (MIND) that aligns with the APA categories but includes objective and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 27 publications
0
63
0
Order By: Relevance
“…Secondly, there is no consensus approach to evaluating mHeath apps (Torous et al 2018 ). A recent scoping review found the MIND categories and questions largely overlap with content encompassed in other existing app evaluation frameworks, suggesting good coherence (Lagan et al 2021 ); however, some aspects of user experience (e.g., usability and aesthetic appeal) are not addressed. It has been suggested that the subjectivity inherent in rating such aspects is a likely source of inconsistencies in app evaluations (Carlo et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, there is no consensus approach to evaluating mHeath apps (Torous et al 2018 ). A recent scoping review found the MIND categories and questions largely overlap with content encompassed in other existing app evaluation frameworks, suggesting good coherence (Lagan et al 2021 ); however, some aspects of user experience (e.g., usability and aesthetic appeal) are not addressed. It has been suggested that the subjectivity inherent in rating such aspects is a likely source of inconsistencies in app evaluations (Carlo et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many organizations and academics have developed criteria for evaluating apps, including the author of this paper [13,17,[19][20][21]. However, no matter how comprehensive the criteria, they are both aspirational, incomplete and highly generic.…”
Section: App Evaluation Criteria Are Not Design Criteriamentioning
confidence: 99%
“…More than 200 healthcare applications (apps) for smartphones and tablets are uploaded daily to Apple's App Store and Google Play [60] (p. 93). Approximately 300,000 health apps are currently available, of which 10,000 to 20,000 are mental health apps [61,62]. These publicly available apps are opening further opportunities to provide mobile healthcare (mHealth) anytime, anywhere.…”
Section: App-based Cognitive Behavioral Therapymentioning
confidence: 99%
“…This need has led to the development of app-rating guidelines, such as the Mobile App Rating Scale (MARS) and the American Psychiatric Association's app evaluation framework [83,84]. Unfortunately, the increasing number of app evaluation frameworks makes it difficult for clinicians and patients to select an appropriate evaluation framework and find an appropriate mental health app [62]. Therefore, app-rating platforms, such as PsyberGuide, have gone one step further by identifying, describing, and rating publicly available mental health apps [85].…”
Section: App-based Cognitive Behavioral Therapymentioning
confidence: 99%